Combination of Isoniazid and Rifampin for the Prevention of Failure of Standard Therapy for Latent Tuberculosis Infection in Children: Evidence Base Case Report - Bakhtiar Bakhtiar; Hirsa Angriani (The Faculty of Veterinary Medicine of Syiah Kuala University, 2021)
Tuberculosis (TB) control program in children is carried out with three strategies: finding and treating adult TB cases (as a source of transmission), treating latent TB infection, and administering the BCG vaccine. There is a high risk of transmission in children in close contact and living at home with adult patients. After Mycobacterium is inhaled through the respiratory tract, then the body's resistance to Mycobacterium tuberculosis occurs. Furthermore, there are two possibilities: only TB infection occurs, or the child has TB disease. We report one case: a boy, age four years, diagnosed with latent TB infection. This diagnosis is based on the findings of the 13 mm tuberculin test (positive). There is a history of contact with adult TB patients. On physical examination, no abnormalities were found. Likewise, the chest X-ray examination also found no abnormalities. Due to the diagnosis of latent TB infection, prophylaxis with Isoniazid was planned for six months. In the first month, the child still wants to take medication according to the rules. However, entering the second month, children sometimes do not want to take medication. This situation raises concerns about the possibility of therapy failure. His mother was very worried about this condition. Therefore, doctors offer to provide a combination pattern of therapy in isoniazid with rifampicin, with a span of 3 months. Standard therapy with INH alone was discontinued. This therapeutic decision was based on a study that combined INH with rifampin for three months gave better results than single prophylactic therapy with INH.